Hippocampal damage increases deontological responses during moral decision making. - McCormick, C; Rosenthal, C; Miller, T; Maguire, E (Society for Neuroscience, 2016)
Complex moral decision making is associated with the ventromedial prefrontal cortex (vmPFC) in humans, and damage to this region significantly increases the frequency of utilitarian judgments. Since the vmPFC has strong anatomical and functional links with the hippocampus, here we asked how patients with selective bilateral hippocampal damage would derive moral decisions on a classic moral dilemmas paradigm. We found that the patients approved of the utilitarian options significantly less often than control participants, favoring instead deontological responses-rejecting actions that harm even one person. Thus, patients with hippocampal damage have a strikingly opposite approach to moral decision making than vmPFC-lesioned patients. Skin-conductance data collected during the task showed increased emotional arousal in the hippocampal-damaged patients and they stated that their moral decisions were based on emotional instinct. By contrast, control participants made moral decisions based on the integration of an adverse emotional response to harming others, visualization of the consequences of one's action, and the rational re-evaluation of future benefits. This integration may be disturbed in patients with either hippocampal or vmPFC damage. Hippocampal lesions decreased the ability to visualize a scenario and its future consequences, which seemed to render the adverse emotional response overwhelmingly dominant. In patients with vmPFC damage, visualization might also be reduced alongside an inability to detect the adverse emotional response, leaving only the utilitarian option open. Overall, these results provide insights into the processes involved in moral decision making and highlight the complementary roles played by two closely connected brain regions. SIGNIFICANCE STATEMENT: The ventromedial prefrontal cortex (vmPFC) is closely associated with the ability to make complex moral judgements. When this area is damaged, patients become more utilitarian (the ends justify the means) and have decreased emotional arousal during moral decision making. The vmPFC is closely connected with another brain region-the hippocampus. In this study we found that patients with selective bilateral hippocampal damage show a strikingly opposite response pattern to those with vmPFC damage when making moral judgements. They rejected harmful actions of any kind (thus their responses were deontological) and showed increased emotional arousal. These results provide new insights into the processes involved in moral decision making and highlight the complementary roles played by two closely connected brain regions.